Microbial epidemiology and carriage studies for the evaluation of vaccines. Issue 10 (16th August 2019) - Coughtrie, Abigail L.; Jefferies, Johanna M.; Cleary, David W.; Doncaster, C. Patrick; Faust, Saul N.; Kraaijeveld, Alex R.; Moore, Michael V.; Mullee, Mark A.; Roderick, Paul J.; Webb, Jeremy S.; Yuen, Ho Ming; Clarke, Stuart C.
Abstract : Respiratory tract infections are responsible for over 2.8 million deaths per year worldwide. Colonization is the first step in the process of microbes occupying the respiratory tract, which may lead to subsequent infection. Carriage, in contrast, is defined as the occupation of microbial species in the respiratory tract. The duration of carriage may be affected by host immunity, the composition and interactions between members of the microbial community, and the characteristics of colonizing bacteria, including physiology associated with being present in a bacterial biofilm. Numerous vaccines have been implemented to control infections caused by bacteria that can colonize and be subsequently carried. Such vaccines are often species-specific and may target a limited number of strains thereby creating a vacant niche in the upper respiratory tract. Epidemiological changes of bacteria found in both carriage and disease have therefore been widely reported, since the vacant niche is filled by other strains or species. In this review, we discuss the use of carriage-prevalence studies in vaccine evaluation and argue that such studies are essential for (1) examining the epidemiology of carriage before and after the introduction of new vaccines, (2) understanding the dynamics of the respiratory tract flora and (3) identifying the disease potential of emerging strains. In an era of increasing antibiotic resistance, bacterial carriage-prevalence studies are essential for monitoring the impact of vaccination programmes.